Educational Management in Nigeria: Issues and Way-Forward (International Journal of Educational Management, Rivers State University., 2025)
This paper examined educational management in Nigeria: issues and way-forward. Educational management is a necessity for the advancement of educational programmes and objectives in Nigeria. Effective management is a crucial element that all organisations use in order to enhance production. Management has become a phenomenon and has changed the world’s economic and social landscape. But despite all of these, there are still some emerging issues militating against effective management of education in Nigeria. It is for the above reason that this paper looked into the following concepts, management, concept of educational management, scope of educational management, functions of educational management, educational management as a field, as well as issues in educational management in Nigeria, and the way-forward. It concluded that for Nigeria to achieve the sustainable development goals, the professional status, vibrancy, quality, and competence of planners and managers of education in the country need to be revived and sustained. The paper suggested that government and the private sector should ensure that more effort and resources are made towards effective management of education.